Non-destructive testing in versatile joining processes - Lechner, Michael; Borgert, Thomas; Busch, Matthias; Harms, Arnold; Holtkamp, Pia; Kappe, Fabian; Römisch, David; Wituschek, Simon (Sheet Metal 2025, 2025)
Abstract. Mechanical joints are traditionally analyzed through destructive micrograph analysis, which may compromise internal geometry and morphology, as evidenced by radial cracks in semi-tubular self-pierce riveting. In contrast, industrial X-ray computed tomography (XCT) offers a non-destructive method for component diagnosis, providing volumetric insights without damaging the sample and enabling dimensional measurement. The DFG-funded Collaborative Research Center TRR 285 is exploring XCT’s application in assessing mechanical joinability across various joining processes and materials, particularly in multi-material systems like steel-aluminum joints. XCT faces challenges in accurately capturing multi-material compositions, leading to artifacts that complicate interface detection. This research aims to validate XCT for joint investigations, yielding quantitative characteristics that surpass those from traditional micrograph analysi
Keywords: Computed Tomography; Metrology; Mechanical Joining